Adrenalectomy for incidentaloma: lessons learned from a single‐centre series of 274 patients. Issue 5 (7th July 2017) - Gaujoux, Sébastien; Aimé, Adeline; Assié, Guillaume; Ciuni, Roberto; Bonnet, Stéphane; Tenenbaum, Florence; Bertherat, Jérome; Dousset, Bertrand
Abstract : Background: Adrenal incidentalomas are increasingly diagnosed and include a wide spectrum of lesions from benign adenomas to secreting or malignant lesions. The aim of the present study is to report a large single‐institution experience of patients undergoing surgery for adrenal incidentaloma with particular attention to their diagnosis and post‐operative course and the evolution of surgical practice over time. Methods: From 1993 to 2013, 274 patients underwent adrenalectomy for incidentaloma. All patients underwent standardized clinical, hormonal and imaging assessments. Results: Patients were mainly female (63.1%; n  = 173), and the median age of patients was 56.5 years. After a complete hormonal evaluation, 47.9% ( n  = 129) of incidentalomas were classified as secreting tumours, including 24.4% ( n  = 67) subclinical cortisol‐secreting adenomas and 18.9% ( n  = 52) pheochromocytomas. Adrenocortical carcinomas represented 9.5% ( n  = 26) of incidentalomas, and the risk of malignancy was significantly correlated with tumour size. The conversion rate after laparoscopic adrenalectomy (90.9%; n  = 249) was 3.2% ( n  = 8). The overall morbidity rate was 13.9%, which included a 4.4% rate of severe morbidity (Clavien–Dindo ≥3). From 2008 onwards, there was a significant decrease ( P  < 0.001) in the use of surgical approaches for non‐secreting adenomas. Conclusion: After a complete work‐up, half of the incidentalomas were classified as subclinical oversecreting adrenal lesions and 10% proved to be malignant adrenocortical carcinomas. The debatable use of surgical approaches for benign nonfunctioning adenomas significantly decreased over time.